Coated cysteamine and choline chloride could be potential feed additives to mitigate the harmful effects of fatty liver hemorrhagic syndrome in laying hens caused by high-energy low-protein diet - Muhammad Umar Yaqoob; Yingying Qi; Jia Hou; Li Zhe; Xiangde Zhu; Peng Wu; Zhefeng Li; Minqi Wang; Yan Li; Min Yue (Poultry Science)
ABSTRACT: The research aimed to examine the impact of coated cysteamine (CS) and choline chloride (CC) on relieving the pathological effects of fatty liver hemorrhagic syndrome (FLHS) in laying hens. FLHS was induced by a high-energy low-protein (HELP) diet. Ninety laying hens were equally divided into 5 treatments with 6 replicates per treatment (3 hens/replicate). The control treatment (Cont) was fed a basal diet, while the remaining treatments were fed a HELP diet. Under the HELP dietary plan, 4 treatments were set by a 2 × 2 factorial design. Two levels of CS (CS−: 0.00 mg/kg CS; CS+: 100 mg/kg diet) and 2 levels of choline (CC−: 1,182 mg/kg; CC+: 4,124 mg/kg) were set and named CS−CC− (HELP), CS+CC−, CS−CC+ and CS+CC+. The liver of the CS−CC− (HELP) group became yellowish-brown and greasy, with hemorrhages and bleeding spots. Elevated (P < 0.05) plasma and hepatic ALT and AST and hepatic MDA levels, combined with reduced (P < 0.05) plasma and hepatic SOD and GSH-Px activities in the CS−CC− (HELP) group proved that FLHS was successfully induced. Dietary supplementation of CS, CC, or both (CS+CC+) in HELP diets relieved the pathological changes, significantly (P < 0.05) reduced the AST and ALT levels, and strengthened the antioxidant potential in laying hens under FLHS. The highest (P < 0.001) plasma adiponectin concentration was observed in the CS+CC− and lowest in the CS−CC− (HELP) group. In addition, CS and CC supplementation lowers the elevated levels of hepatic T-CHO and TG by increasing the HDL-C and reducing LDL-C levels (P < 0.05) than CS−CC− (HELP) group. CS supplementation, either alone or with CC, helps laying hens restore their egg production. It could be stated that CS and CC supplements could ameliorate the adverse effects of FLHS by regulating antioxidant enzymes activities, modulating the hepatic lipid metabolism, and restoring the production performance in laying hens. Hence, adding CS and CC could be an effective way to reduce FLHS in laying hens.